2009
DOI: 10.1016/j.patrec.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Mean shift: An information theoretic perspective

Abstract: Abstract-This paper develops a new understanding of mean shift algorithms from an information theoretic perspective. We show that the Gaussian Blurring Mean Shift (GBMS) directly minimizes the Renyi's quadratic entropy of the dataset and hence is unstable by definition. Further, its stable counterpart, the Gaussian Mean Shift (GMS), minimizes the Renyi's "cross" entropy where the local stationary solutions are modes of the dataset. By doing so, we aptly answer the question "What does mean shift algorithms opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…The calculation of the IP was performed per Equation (7). From there, it became necessary to use some technique capable of finding the existing dynamics in the data.…”
Section: Information Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of the IP was performed per Equation (7). From there, it became necessary to use some technique capable of finding the existing dynamics in the data.…”
Section: Information Dynamicsmentioning
confidence: 99%
“…Main researches in ITL include regression, neural network training, classification and clustering [3][4][5][6][7][8][9][10], parameter estimation, system identification and signal processing [11][12][13][14][15][16][17] areas.…”
Section: Introductionmentioning
confidence: 99%
“…In [31] it was shown that the choice of Gaussian kernels is connected with minimization of Renyi's entropy (see Section 3.4). The intuition that mean shift is a form of gradient ascent, which was pointed out in [12], also makes Gaussian kernels attractive since it allows the mean shift algorithm to be defined from a gradient perspective.…”
Section: Mean Shift With Gaussian Kernelsmentioning
confidence: 99%
“…In the following years, the mean shift algorithm met with growing interest in the computer vision community with applications ranging from image segmentation, appearance-based clustering to object recognition and tracking. In recent years, many works have contributed to improve the original mean shift approach [11] [12] [14]. A variable bandwidth mean shift algorithm is proposed in [13].…”
Section: Variable Bandwidth Mean Shiftmentioning
confidence: 99%